Political Occultism in Contemporary Indonesia: Divination, Epistemic Confusion, and the Eclipse of Tawhid - Azfa Muzaki Ali; Agung Pranoto Kadiatmaja (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2026)
The use of political occultism is still prevalent in the political circles of Indonesia in the form of divination, paranormal consultation, talismans, and supernatural claims are some of the ways these practices are being used to support a candidate's political legitimacy. The article uses Muhammad Abid al-Jabiri's views on the different kinds of reasoning as the basis. Moreover, it incorporates Ibn Taymiyyah's distinction between divine and worship-related monotheism. With the aid of qualitative library research, conceptual analysis, source criticism, and philosophical interpreting techniques the researchers have been able to sort out the recorded activities and have also made judgments about their claims for knowledge, theological aspects, and the threats of democracy. The authors state that political occultism is not the same thing as Sufism or 'irfān. A misunderstanding of the epistemic level takes place if individual unchallengeable assertions are transformed into public power without textual supervision, demonstration of proof, or ethical accountability. The article sets up an epistemic-theological grid in which the different functions of moral advising, customary practices, divination, and talismanic protection can be identified, so as to allow an accurate critique of supernatural absolutization without the need to brand the local culture as a whole.